2022
DOI: 10.1177/13623613221123712
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators for obtaining support services among underserved families with an autistic child: A systematic qualitative review

Abstract: Families of autistic children from underserved populations participate in support services at lower rates than other families. To better understand possible reasons for this inequity, we reviewed qualitative studies examining parent-reported barriers and facilitators to accessing and participating in support services. A systematic search identified 18 articles that met inclusion criteria. Resulting thematic analysis located three themes: (a) support service accessibility, (b) diversity of support services, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 60 publications
6
8
0
Order By: Relevance
“…In addition, caregivers from non‐CALD backgrounds were over three times as likely to report difficulties in accessing NDIS services, and were more likely to report lack of knowledge as a barrier to accessing interventions, compared to CALD caregivers. While counter‐intuitive at face value, given that some literature suggests families from CALD backgrounds experience difficulties accessing support services (Wallace‐Watkin et al, 2022), this finding aligns with our recent research investigating predictors of diagnostic delay, where children from CALD backgrounds received diagnoses earlier than those from non‐CALD backgrounds (Boulton, Hodge, et al, 2023). Indeed, it is possible that the CALD caregivers in this cohort are well‐versed in navigating various governmental access systems, and may have be better educated and equipped to navigate some of the bureaucratic hurdles that can be associated with the NDIS, relative to their non‐CALD counterparts.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In addition, caregivers from non‐CALD backgrounds were over three times as likely to report difficulties in accessing NDIS services, and were more likely to report lack of knowledge as a barrier to accessing interventions, compared to CALD caregivers. While counter‐intuitive at face value, given that some literature suggests families from CALD backgrounds experience difficulties accessing support services (Wallace‐Watkin et al, 2022), this finding aligns with our recent research investigating predictors of diagnostic delay, where children from CALD backgrounds received diagnoses earlier than those from non‐CALD backgrounds (Boulton, Hodge, et al, 2023). Indeed, it is possible that the CALD caregivers in this cohort are well‐versed in navigating various governmental access systems, and may have be better educated and equipped to navigate some of the bureaucratic hurdles that can be associated with the NDIS, relative to their non‐CALD counterparts.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, caregivers who reported a lack of knowledge about where to go and who to contact as a barrier to accessing interventions were more likely to have lower levels of education and live in geographically disadvantaged areas. These findings align with prior work evaluating barriers to accessing interventions post‐diagnostic assessment, where socioeconomic status consistently emerges as a key access barrier (Wallace‐Watkin et al, 2022, 2023). Taken together, these findings suggest that socioeconomic status is an important driver of difficulties in accessing interventions while families wait for a developmental assessment.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Survey development. The survey used in this study was based on the results of a qualitative systematic literature review (Wallace-Watkin et al, 2023). This review, conducted collectively by the authors, examined parent reported barriers and facilitators for accessing and/or participating in support services for autistic children from underserved families.…”
Section: Methodsmentioning
confidence: 99%